Does corporate diversity really matter in the plantation sector? Empirical evidence from a world islamic leading country and market reaction - Rohail Hassan; Maran Marimuthu (International Journal of Financial Studies, 2017)
The paper examines demographic and cognitive diversity at top-level management and its impact on the performance of Malaysian-listed companies (Plantation and Energy Sectors). Although many organisations aspire to be socially diverse, diversity's consequences for organisational performance remain unclear. Do profitable firms tend to enhance board diversity or other attributes of the firm that contribute towards the firm's financial performance? This study specifies the whole distinct mechanism and measures it independently; bridging as the demographic and cognitive diversity among the board of directors (BODs) and bonding as the firm's financial performance. To maintain the homogeneity factor, empirical analysis is confined to two fully-fledged sectors and 125 Malaysian listed firms out of 798 firms selected on the basis of judgmental sampling during the period of 2009 to 2013. The paper applies econometrics methodology on panel data analysis and the correlation matrix to justify this phenomenon. The paper attempts to fill the gap in the existing literature, discuss the empirically diverse corporate boards with the interaction approach and its impact on firm performance (a) gender diversity and foreign participation (b) gender diversity and ethnic diversity. The empirical findings suggest that both demographic and cognitive diversity are significant predictors of a firm's financial performance. Hence, the companies specifically belonging to plantation and energy sectors are more responsible for promoting diversity among top-level management.
Keywords: M1; M14; G3; G34; 330; demographic diversity; gender diversity; ethnic diversity; age profile; cognitive diversity; board of directors (BODs); education diversity; Tobin's Q; market performance